PENGEMBANGAN PARIWISATA MELALUI NILAI BUDAYA BERWAWASAN LINGKUNGAN BUDAYA, PARADIGMA BARU SIMBIOSIS MUTUALISME - Roro Dwi Sulistyowati (Jurnal Terapung : Ilmu - Ilmu Sosial, 2021)
Culture is very closely related to tourism, because we can see from the definition of culture which is a symbol of the surrounding community around which there is a meaning that includes everything that is the result of creation, human work. Meanwhile tourism is a series of trips undertaken by a person or group of people outside their temporary residence for various purposes (such as vacationing, enjoying the beauty of nature and culture, business, etc. Then we can see that the relationship between cultures has a relationship that is very closely related to tourism and the cultural environment which can provide added value to tourists who come to visit the place.We can also conclude that tourism and culture are activities of exchanging information and cultural symbols in which there are places, traditions, arts, ceremonies, and other identities contained in the place that can be enjoyed by every tourist who comes to visit.Keywords: tourism development, cultural values, cultural environment.